Experimental Analysis of Different Control Methods for the Speed Control of Alternative-Current Servo Motors - (:unkn) unknown (PRAISE WORTHY PRIZE SRL, 2011)
This paper focused on increasing the control performance of alternative-current servo motor (ACSM) drive by solving problems occurring during the speed control of this motor widely used in many industrial areas. The speed control of ACSM was implemented by a vector-controlled drive controlled by means of the designed external controllers. For this aim, firstly, the equations of ACSM were obtained by deriving mathematical model of permanent-magnet synchronous motor used as ACSM. Then, Proportional-integral, proportional-integral-derivative, fuzzy logic, and adaptive artificial neuro-fuzzy inference system controllers were designed. These controllers were applied into the simulation and experimental studies under different load and speed conditions, and the results of ACSM drive were illustrated. Copyright (C) 2011 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: AC Servo Motor; Proportional-Integral; Proportional-Integral-Derivative; Fuzzy Logic; Adaptive Artificial Neuro-Fuzzy Inference System